P062 Histone deacetylase 1 (HDAC1): a novel therapeutic target in rheumatoid arthritis. (March 2019) - Goschl, L; Saferding, V; Kugler, M; Backlund, J; Mathias, P; Scheinecker, C; Ellmeier, W; Günter, S; Bonelli, M
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: Despite enormous efforts to develop new therapeutic strategies, a large number of patients with Rheumatoid Arthritis (RA) do not sufficiently respond to currently available drugs, which underlies the unmet need to identify new therapeutic targets. CD4 + T cell subsets have been shown to be major drivers of inflammation in RA patients. The expression of their key transcription factors is controlled by histone modifications which includes acetylation of lysine residues mediated by histone deacetylases (HDAC). Pan HDAC inhibitors have been shown to be a potential therapeutic strategy for the treatment of multiple myeloma and cutaneous T cell lymphoma. However, major side effects limited the clinical use. We therefore addressed the individual role of HDAC1 in a murine arthritis model. Methods: Mice with a T cell specific deletion of HDAC1 (HDAC1cKO) were generated by using the CD4Cre/LoxP system. Collagen-induced arthritis (CIA) was induced at week 8. Animals were scored for paw swelling and grip strength. After 10 weeks, mice were sacrificed and paraffin sections of the affected joints were analyzed for histomorphologic signs of inflammation, cartilage and bone destruction. Anti-CII antibody levels were determined by ELISA. To further investigate antibody switch, we performed a DNP-KLH immunization. Serum samples were analyzed for cytokines by multiplex assays. CCR6 expression in CD4 + T cells was analyzed by flow cytometry. Transcriptomic analysis from existing RNA-seq was performed in naïve T cells and ex vivo isolated Th17 cells from WT mice and STAT3 -/- mice. Binding of STAT3 to the CCR6 locus was analyzed from previously published STAT3 ChIP-Seq data of IL-6 treated CD4 + T cells. Results: After induction of CIA, HDAC1-cKO mice showed no clinical or histological signs of arthritis. After immunization either with collagen or the model antigen KLH, WT and HDAC1-cKO mice kept regular antibody production, which suggests an undisturbed T cell – B cell interaction. The inflammatory cytokines IL-17 and IL-6 were significantly decreased in HDAC1-cKO mice. In addition, CCR6 upregulation was significantly impaired in HDAC1 deficient CD4 + T cells, when cultured in the presence of IL-6. Under these conditions, binding of STAT3 to the CCR6 gene locus was detected. Consecutively CCR6 expression was significantly lower in CD4 T cells isolated from STAT3 -/- mice as compared to WT mice. Conclusions: Our data show the importance of HDAC1 as a key immune regulator in the pathogenesis of T cell driven collagen induced arthritis. Therefore, it might be considered as an interesting novel therapeutic target in RA. Disclosure of Interest: None declared.